Youth and Social-Media: The Adaptation of Dangdut Koplo Song in Islamic Da’wah - Nuryani Nuryani; Darsita Suparno; Syihaabul Hudaa; Kundharu Saddhono (Buletin Al-Turas, 2021)
The purpose of this study was to describe the role of youth in adapting dangdut koplo songs to songs that have da’wah value, and the the relationship between popular culture and religion in the adapted songs. Purposively, this qualitative study relied on some lyrics of dangdut koplo songs adapted by the into more religious ones. In analyzing the data, the researcher used the theory of cultural adaptation, social media, and Roland Barthes’ semiotics. The research found out the youth adapted the lyrics from dangdut koplo into religious dangdut by changing the lyrics with the same arrangement. This was done so that people remained familiar with the dangdut music they enjoyed with a touch of religion. The devotional lyrics were characterized by advice, advocating goodness, encouraging people to stay away from evil, loving the prophet more, and social criticism. Regarding the distribution patterns of the adapted songs, there were two dominant media utilized, YouTube channels and Taklim assembly which was usually done by santri and non-santri youth. This showed that in the process of adaptation and dissemination, the adolescents played as an adaptation agent, distribution agent, and agent of change. The study concluded the adapted religious dangdut koplo songs could be an interesting media in the millennial da’wah.